Salpingectomy before assisted reproductive technologies: a systematic literature review. Issue 1 (December 2016) - Noventa, Marco; Gizzo, Salvatore; Saccardi, Carlo; Borgato, Shara; Vitagliano, Amerigo; Quaranta, Michela; Litta, Pietro; Gangemi, Michele; Ambrosini, Guido; D'Antona, Donato; Palomba, Stefano
Abstract Salpingectomy is largely used in case of hydrosalpinx in infertile women scheduled for assisted reproductive technologies (ART), whereas there is no consensus on its role in absence of hydrosalpinx. The current is a systematic literature review to collate all available evidence regarding salpingectomy as fertility enhancement procedure before ART in infertile patients. Our primary endpoint was to assess the impact of the surgical procedure on ovarian reserve, and secondary outcomes were to evaluate its benefits and harms on ART outcomes. We identified 29 papers of which 16 reporting data on the impact of tubal surgery on ovarian reserve and 24 (11 previously included) on ART outcomes. Available data suggested an absence of variation in ovarian reserve markers after unilateral salpingectomy while contradictory results were reported for bilateral surgery. Considering ART outcomes, data reported a significant improvement in ongoing pregnancy/live-birth rate in treated subjects without significant reduction in ovarian response to gonadotropin stimulation. In case of tubal disease, a surgical approach based on unilateral salpingectomy may be considered safe, without negative effects on ovarian reserve and ovarian response to controlled ovarian stimulation whilst having a positive effect on pregnancy rate. Data regarding bilateral salpingectomy and ovarian reserve are conflicting. Further trials are needed to confirm both the benefits of salpingectomy before ART and the safety of bilateral salpingectomy on ovarian reserve, and to clarify the role of uni- or bilateral surgery in case of tubal blockage without hydrosalpinx.